Prospects for the Application of Probiotics to Increase the Efficiency of Integrated Cultivation of Aquatic Animals and Plants in Aquaponic Systems - Dmitry Rudoy; Anastasiya Olshevskaya; Victoria Shevchenko; Evgeniya Prazdnova; Mary Odabashyan; Svetlana Teplyakova (Fishes)
Aquaponics is an integrated method of aquatic animal and plant cultivation in a closed recycling system where the wastewater from aquatic animals is purified by microbes, which transform pollutants into nutrients for plants at the end of the chain. This technology allows to the efficiency of the area to be increased by a combination of cultivated plants and aquatic animals. Aquaponics produces environmentally friendly products by reducing fertilizer use and wastewater volume, increasing the extent of reuse by up to >90%. A promising way to increase efficiency in aquaponics is to use bacterial preparations (probiotics). This will allow control of the development of pathogens in the growing system, improving water quality and the growth rate of aquatic organisms. This paper overviews the experience of using probiotic preparations in aquaponic systems. It is shown that probiotics are able to increase the survival rate of aquatic organisms, improve the hydrochemical regime in recirculating aquaculture systems, and mitigate the risk of pathogenic contamination. There are a number of problems in aquaponics that prevent it from becoming more widespread and achieving maximum productivity, including problems with optimal pH and temperature, problems with nutrient and oxygen depletion, as well as diseases caused by phytopathogens and fish pathogens. The probiotics used do not take into account the biological needs of all components of the aquaponic system. The development of probiotic preparations from soil bacteria of the genus Bacillus will allow us to create a new class of probiotics specifically for aquaponics. Such preparations will work in a wide pH range, which will allow us to achieve maximum productivity for all components of aquaponics: animals, plants and bacteria.